Gambaran Religiusitas Pada Remaja Yang Kecanduan Minuman Keras (Alkohol) di Desa “X” - Kusuma, Dinar Sulistyaning; Hasanah, Muhimmatul; Wicaksono, Awang Setiawan (Populer: Jurnal Penelitian Mahasiswa, 2024)
The highest level of alcohol consumption in education is among students. One of the factors causing the increase in alcohol consumption behavior and the rise in crime cases due to alcohol consumption is a lack of religiosity. Religiosity as the internalization of religious values related to belief in religious teachings. These beliefs are then actualized in human behavior. This research is included in the type of qualitative research with a case study approach. The conceptual boundaries of this research are religiosity, teenagers aged 18 - 21 years, and subjects who live in Village "X". The subjects in this research were teenagers who were alcoholics, both male and female, totaling 5 subjects. In this research, nonprobability sampling technique was used with purposive sampling. Subjects have a level of belief in God, religion and sin in their religion. Having high intentions can influence the subject's level of commitment to carrying out ritualistic activities. Subject knowledge regarding religious knowledge is fulfilled through developing digital media. Subjects' feelings towards ritual activities and their experiences of consuming alcohol vary. subject, no one mentioned behaving well because they were motivated by the teachings of their religion. All subjects felt comfortable with the circle of friends that the subjects were now living in. Factors that influence individuals to consume alcohol are environmental factors and the individual's own desires.